2017
DOI: 10.1016/j.seizure.2017.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of side effects of anti-epileptic drugs (AEDs) in adults with intellectual disability: A systematic review

Abstract: Epilepsy AED Side-effect PROM Highlights Out of a total of 108 measures identified, only eight were appropriate for use with people with ID. Screening tools are available to assess AED side effects in general adult populations; there are only two measures specifically designed for use in ID populations. The focus of these measures is broader than side effects and so may not pick up the full range of side effects of importance in this group. Side effects of AEDs are inconsistently and inadequately measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 84 publications
0
5
0
1
Order By: Relevance
“…94 A systematic review of tools to measure side effects of AEDs highlighted that, of 108 measures identified, only 8 were appropriate for use in adults with ID, and only 2 measures had been designed for use in people with ID. 95 As a result, side-effect detection is likely to be overly reliant on carer reports and side effects remains under detected. This represents a challenge for doctors, pharmacists and other health professionals in assessing the efficacy and safety of treatment in adults with epilepsy.…”
Section: Antiepileptic Drugsmentioning
confidence: 99%
“…94 A systematic review of tools to measure side effects of AEDs highlighted that, of 108 measures identified, only 8 were appropriate for use in adults with ID, and only 2 measures had been designed for use in people with ID. 95 As a result, side-effect detection is likely to be overly reliant on carer reports and side effects remains under detected. This represents a challenge for doctors, pharmacists and other health professionals in assessing the efficacy and safety of treatment in adults with epilepsy.…”
Section: Antiepileptic Drugsmentioning
confidence: 99%
“…Bu çalışmalardan dört tanesinde LTG entellektüel disabilite üzerine etkisiyle ilgili olup, sadece bir çalışmada LTG'nin yan etki olarak emosyonel değişiklik yaptığı izlenmiştir. [33,34] Literatürden anlaşıldığı gibi antiepileptik ilaçların çocuk ve erişkinlerde sağlıklı ve epileptik bireylerde davranış üzerine etkileri net olarak bilinmemektedir, bu konuda yapılan çalışmalar halen yetersiz görülmektedir.…”
Section: Discussionunclassified
“…A recent review by Copeland et al examined measurement tools for adverse medication effect assessment in people with ID. However, this article focuses exclusively on rating scales designed to assess anti-epileptic adverse effects, as opposed to examining adverse medication effect scales in its entirety [ 61 ]. This review adopted a more comprehensive approach, with all medication-related adverse effects scales that are established as applicable, or potentially could be applicable to people with ID with appropriate adaptations, being examined.…”
Section: Strengths and Limitationsmentioning
confidence: 99%